Response and adaptations made by the integrated child development services stakeholders towards the digitalisation of its record keeping systems of the Anganwadi centres in urban Gujarat, India - Kurian, Sneha; Chawada, Bansari L (International Journal Of Community Medicine And Public Health, 2023)
Initiated on 12th February 2018, Anganwadi centres (AWC) of Gujarat adapted the integrated child development services common application software (ICDS-CAS), for real time monitoring and record keeping, for Anganwadi workers (AWWs), Anganwadi supervisors (AWS) and the child development project officers (CDPO).This application was abruptly discontinued in September 2020 and replaced by ‘Poshan tracker’ ,a mobile based application, launched by the ministry of women and child development, government of India on 1st March 2021. Documentation of challenges and benefits due to shift to software-based record keeping system by frontline workers of ICDS in urban Gujarat. Informal meetings were held with stakeholders like the CDPO, AWS and AWWs to discuss the challenges faced due to digitalisation of record maintenance. We planned to conduct two focused group discussions (FGD) for the same purpose. FGDs were conducted at two different Anganwadi, within city corporation area. Audio recordings of both FGDs were repeatedly played and analysed to prepare qualitative report. ‘ICDS-CAS’ didn’t store older records so the AWWs had to refer to their older registers. The software was English based but AWWs preferred Gujarati(local) language. ‘Poshan tracker had no ‘auto-update’ and ‘delete’ option, to rectify inaccurate entries. One could easily view all the information in one glance. Software database had compiled data from anganwadi, removing the need for supervisors to separately contact each AWWs for an anganwadi data. It was concluded that elder AWWs preferred old register entry system, while the younger AWWs preferred the software data entry system.